A finite-time convergent dynamic system for solving online simultaneous linear equations. Issue 9 (2nd September 2017) - Xiao, Lin; Liao, Bolin; Jin, Jie; Lu, Rongbo; Yang, Xi; Ding, Lei
ABSTRACT: A new dynamic system is proposed and investigated for solving online simultaneous linear equations. Compared with the gradient-based dynamic system and the recently proposed Zhang dynamic system, the proposed dynamic system can achieve superior convergence performance (i.e. finite-time convergence) and thus is called the finite-time convergent dynamic system. In addition, the upper bound of the convergence time is derived analytically with the error bound being zero theoretically. Simulation results further indicate that the proposed dynamic system is much more efficient than the existing dynamic systems.